The Relationship Between Mothers’ Interests and Multiple Immunization in Rejoslamet Village - Fitrah Ningtyas, Septi; Mudhawaroh; Grah Prihartanti, Niken; Sulistiawati, Erni (Jurnal KESANS : Kesehatan dan Sains, 2025)
Immunization is a proactive measure to boost the immune system's ability to ward off or significantly reduce the severity of certain illnesses.  Infant mortality rate (IMR) and vaccine-preventable disease (VPD3I) risk are both exacerbated by children's incomplete repeated vaccinations.  Knowledge, attitude, and interest all have a role on how well a person completes multiple immunizations.  community, family, and traditional practices; family variables include mother age, education, hobbies, income, and profession; and community aspects include health care resources.  When it comes to making sure that kids are vaccinated, maternal interests play a big role.  Using observational analytics and a cross-sectional research methodology, this study seeks to ascertain the association between mother interest and the completion of various vaccines for children at the Rejoslamet Integrated Health Post (Integrated Health Post) in Jombang District.  Structured questions on maternal interest in the completeness of multiple vaccines and studying the KIA book were added in the questionnaire that was given to 42 women at the Rejoslamet village Integrated Health Post (Integrated Health Post), Jombang District.  A combination of successive sampling and univariate and bivariate statistical analysis was used to analyze the collected data.  At the Rejoslamet village Integrated Health Post (Integrated Health Post), Jombang District, a p value of 0.000 indicated a significant association between mother desire and the completion of multiple immunizations for children